Multidisciplinary education with a focus on COPD in primary health care - Alcântara, Erikson Custódio (J Bras Pneumol, 2019)
OBJECTIVE: To evaluate the use of video lessons on the topic of COPD as a training tool for a multidisciplinary team working in the primary health care sector. METHODS: This was a quasi-experimental study involving a multidisciplinary team working at a primary health care clinic. The level of knowledge about COPD was measured by applying a specific, 16-item questionnaire - before, immediately after, and three months after the video lessons. In a set of six structured video lessons, the training focused on the prevention, case-finding, treatment, and monitoring of cases of COPD. The data were analyzed with the Friedman test, the Kruskal-Wallis test, Tukey’s post hoc test, Dunnett’s test, and the Bonferroni test. RESULTS: There was a significant difference between the periods before and immediately after the training in terms of the scores on 15 of the 16 items on the questionnaire regarding the level of knowledge about COPD. The median total score of the participants increased significantly, from 60 points before the training to 77 points immediately thereafter and 3 months thereafter (p < 0.001 for both). Before the training, 23 (63.9%) and 13 (36.1%) of the members of the multidisciplinary team presented strong and very strong levels of agreement, respectively, among the 16 questionnaire items. After the training, 100% of the individuals presented a very strong degree of agreement. CONCLUSIONS: Multidisciplinary education through video lessons increased the knowledge of COPD on the part of a primary health care team, and the knowledge acquired was retained for at least three months after the intervention.